Study on Estimation and Antioxidant activity of Gloriosa superba L. Whole Plant Extract - Jothi, U.; Jebamalar, J. Angelin; Sivakumar, T. (International Journal of Scientific Research in Biological Sciences, 2019)
Gloriosa superba is a alkaloid plant, which contains alkaloid components such as colchicine and gloriosine. In this study, Total Phenol content (TPC), Total Flavonoid (TF), Free radical scavenging activity (DPPH) using whole plant (Shoot, Flower, Tuber (SFT) extract derived from G. superba were tested for cancer. G. superba plants are identified and collected. The collected plants were separated into (SFT) G. superba whole plants are dried under the laboratory conditions. The temperature associated with the solvent used in the powder sampling will be followed by extraction using the different conical flask for 1 week and filtered what Mann No.1 paper. The filtrate was stored and used for further experimentation. Analysis of solvent extracts was subjected to phytochemical and antioxidative activity of DPPH assay. Different concentrations such as 20μg, 40μg, 60 μg, 80 μg and 100 μg were taken for all studies and the values are entered in terms of Mean±SD. In case of DPPH assay IC50 values are calculated using ANNOVA. Methanolic extraction from each solvent contains a high value of antioxidant properties.